Australia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Economic growth is strengthening, stimulated by the high terms of trade. Monetary policy has been tightened appropriately. A flexible monetary policy response to potential external shocks, including commodity price swings, will help to cushion growth while preserving low inflation. To promote robust risk management practices by financial institutions, the government intends to conduct further stress tests and review the regulation of banks' liquidity. The recent surge in revenues provides resources that should be used for the implementation of reforms in sustaining strong economic growth.